PENINGKATKAN HASIL BELAJAR LARI SPRINT MELALUI VARIASI PEMBELAJARAN SISWA KELAS VIII SMP NEGERI 2 MEDAN - Ikram Anwar; Sabaruddin Yunis Bangun (Indonesia Sport Journal, 2019)
This study aims to determine the Improved Learning Outcomes of Sprints Using Learning Variations in Class VIII Students of SMP Negeri 2 Medan Academic Year 2018/2019. The subjects in this study were students of class VIII with 32 students. The method used in this research is Classroom Action Research using a quantitative approach. From preliminary Sprint data using variations in overall learning outcomes There are only 10 students who understand the basic techniques of sprint running (31.25%), the remaining 22 students still cannot understand how to do the sprints starting from the beginning, implementation and suffixes ie around (68.75%). Cycle I obtained as many as 22 students (68.75%) have reached the level of mastery learning while 10 students have not reached the level of mastery learning (31.25%), but have not met the expected classical completeness criteria of 75%. Cycle II as many as 27 students (84.37%) who have achieved mastery learning and 5 students are still incomplete (15.63%). The conclusion of the research is that through variations in learning can have an effect in efforts to improve learning outcomes for sprint running in class VIII SMP Negeri 2 Medan Academic Year 2018/2019.